Fat phobia scale-short form and beliefs about obese persons scale: cross-cultural adaptation to Brazilian Portuguese - de Souza, Gabriela Cristina Arces; Laus, Maria Fernanda; da Silva, Wanderson Roberto [UNESP]; Japur, Camila Cremonezi (Springer Nature, 2024)
The Fat Phobia Scale-Short Form (FPS) and the Beliefs About Obese Persons Scale (BAOP) are scales developed to investigate fatphobia and beliefs about obese persons, respectively. The aim of the study was to carry out the cross-cultural adaptation of these scales to Brazilian Portuguese. The methodology was carried out in 5 stages: 1. translation, 2. synthesis of translations, 3. evaluation by the expert committee of semantic, idiomatic, experiential and conceptual equivalences, 4. discussion with the target population (health professionals and other areas), and 5. back-translation. The results of the judgment of equivalences evaluated by the specialists were presented in absolute and relative frequency, and the agreement of the results between the specialists was verified by the Kappa de Fleiss Coefficient (₭). The results showed excellent agreement for all equivalences in both scales, except for BAOP semantics, which was good. (₭ = 0.67). Suggestions from the target population (Brazilian adults) were considered to adapt the final version of the two scales, which were back-translated and approved by the original authors. It is concluded that FPS and BAOP are duly adapted to Brazilian Portuguese and ready to be tested for their psychometric qualities.
Keywords: Obesity; Questionnaires; Weight bias; Weight prejudice